Analisis Integrasi Teknologi dalam Pembelajaran Matematika terhadap Kemampuan Penalaran Matematis Siswa - Nurfadilah, Nurfadilah; Suradi, Suradi; Danial, Danial (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the influence of technology integration in mathematics learning on students’ mathematical reasoning abilities at the secondary education level. The study employs a literature review method by analyzing 15 relevant research studies published between 2015 and 2025. The analysis reveals that the integration of technology in mathematics instruction, such as the use of GeoGebra, Edmodo, Kahoot, Wordwall, Macromedia Flash, Augmented Reality (AR), and the Flipped Classroom model has a positive and significant effect on improving students’ mathematical reasoning skills. The use of educational technology enables students to interact with mathematical concepts visually, dynamically, and interactively, thereby strengthening their logical, analytical, and reflective thinking abilities. Furthermore, the effectiveness of technology-based learning is influenced by internal factors, such as intelligence and learning motivation, as well as external factors, including environmental support and the teaching methods employed by educators. Overall, the findings indicate that the integration of technology in mathematics learning serves as an innovative and effective strategy to enhance students’ mathematical reasoning abilities across various educational levels. Keywords: Educational Technology, Mathematical Reasoning Ability, Literature Review.